Finding NEMO: A bifurcated pathway of NF-B activation occurs via the recruitment of NEMO to polyubiquitin scaffolds at TCR - DeRiso, Elizabeth. (2017)
Abstract: Recent advancements in the field of cancer immunotherapy take advantage of T cell signaling controls, highlighting the importance of fully understanding basic signaling mechanisms for therapeutic targeted use. The NF-κB essential modulator protein (NEMO), also known as IKKγ, regulates canonical activation of the pro survival and growth transcription factor, NF-κB, downstream of the T cell receptor (TCR). Patients with mutated or deficient NEMO protein generally present with some form of immunodeficiency. Despite this key role of NEMO in immunity, however, little is known about the specific mechanisms regulating the sub-cellular localization of NEMO during immunoreceptor signaling. Using high-resolution, dynamic confocal microscopy, we analyzed the localization of NEMO in response to TCR ligands in primary human T cells, as well as leukemic Jurkat T cells. Our model system consists of a glass surface coated with anti-CD3 ligand (OKT3) and the VLA-4 ligand rhVCAM1, used to mimic the stimulatory surface of an antigen presenting cell (APC). Using fluorescently tagged chimeric proteins, we can image the interface between the T cell and the glass to determine where NEMO and other TCR-proximal signaling proteins localize within the immunological synapse. We demonstrate that NEMO is recruited into functionally relevant, ubiquitin-dependent microclusters that co-localize with the TCR-associated kinase Zap70. Recruitment of NEMO into Zap70 clusters occurs within five minutes of TCR engagement, indicating rapid recruitment of NEMO to the TCR. We also demonstrate that IKK, the kinase relevant for NF-B activation, is recruited and activated in the microcluster. Additionally, NEMO is recruited into mobile vesicles and larger, slow moving, membrane-bound macroclusters. Entrance of NEMO into microclusters is also dependent on Zap70 and Lck kinase activity, yet is independent of other proximal signaling molecules such as SLP76 and LAT. Furthermore, we show that NEMO recruitment into microclusters occurs independent of CBM complex member CARMA1, and did not specifically co-localize with BCL10 polymers. We propose a shift away from the normal antigen stimulated NF-B pathway paradigm with assumed cytosolic localization of NEMO. Instead, our results suggest that the mechanisms responsible for NEMO recruitment to the TCR and for the subsequent activation of NF-κB must diverge downstream of Zap70 before rejoining later at an unknown point.; Thesis (Ph.D.)--Tufts University, 2017.; Submitted to the Dept. of Immunology.; Advisors: Stephen Bunnell, and Alexander Poltorac.; Committee: Joan Mecsas, Marta Gaglia, and Hao Wu.; Keyword: Immunology.